Neurogenomics of the Sympathetic Neurotransmitter Switch Indicates That Different Mechanisms Steer Cholinergic Differentiation in Rat and Chicken Models. (8th May 2012) - Dorn, Roland; Loy, Bernhard; Dechant, Georg; Apostolova, Galina
Abstract : Vertebrate sympathetic neurons have the remarkable potential to switch their neurotransmitter phenotype from noradrenergic to cholinergic—a phenomenon that has been intensively studied in rat and chicken models. In both species, loss of noradrenergic markers and concomitant upregulation of cholinergic markers occurs in response to neuropoietic cytokines such as ciliary neurotrophic factor (CNTF). However, other aspects of the neurotransmitter switch including developmental timing, target tissues of cholinergic neurons, and dependence on neurotrophic factors differ between the two species. Here we compare CNTF-triggered transcriptome changes in both species by using DNA microarrays. CNTF induced changes in 1130 out of 16084 analyzed genomic loci in rat sympathetic neurons. When this set of genes was compared to CNTF-induced changes in the chicken transcriptome, a surprisingly small overlap was found—only 94 genes were regulated in the same direction in chicken and rat. The differential responses of the transcriptome to neuropoietic cytokines provide additional evidence that the cholinergic switch, although conserved during vertebrate evolution, is a heterogeneous phenomenon and may result from differential cellular mechanisms.